EXPRESS: Colonization of Helicobacter Species and Associated Gastritis in Cats with Gastrointestinal disease: a Cross-Sectional Study on 154 Cases - Teija Kaarina Immonen; Jenni ME Pettersson; Hanna Vauhkonen; Sara Palen; Ilya Weinstein; Tarja Sironen; Ravi Kant; Antti Kalle Kalervo Sukura; Niina Airas (Journal of Feline Medicine and Surgery, 2026)
Objectives This study aimed to determine the occurrence of gastric Helicobacter species colonization in cats with confirmed gastrointestinal disease and to investigate possible associations between Helicobacter species colonization and gastric histopathological changes. It also aimed to identify the Helicobacter species present in cats in countryX. Methods Privately owned cats were prospectively enrolled between May 2018 and December 2022. Regardless of the reason for presentation, the owners of all cats presented to the cat clinic during that time period were systematically interviewed regarding chronic gastrointestinal signs. Cats with suspected chronic gastrointestinal disease underwent non-invasive diagnostic evaluation, and those with persistent suspicion proceeded to gastrointestinal biopsies. Full-thickness gastric and small intestinal biopsies were collected from each cat to evaluate histopathological lesions and to determine the presence and localization of Helicobacter species in the stomach. A total of 154 cats that underwent biopsies were included in the study. A subset of Helicobacter-positive samples was further analyzed to the species level using the nanopore sequencing technique. Results All cats had chronic small intestinal disease. Of these, 79% had inflammatory enteropathy and 21% had lymphoma. Helicobacter species were detected in 75% of cats. Colonization with multiple Helicobacter species was common, with Helicobacter heilmannii being the most prevalent species. Gastritis was present in 58% of cats and occurred with similar frequency in both small intestinal diseases. The presence of Helicobacter species was significantly associated with lymphoplasmacytic gastritis. However, the density of bacterial colonization was not associated with gastritis severity. Conclusions and relevance Our findings indicate that colonization by Helicobacter species is common in cats with gastrointestinal clinical signs and is associated with chronic lymphoplasmacytic gastritis. Nevertheless, the causal relationship between Helicobacter species and gastritis cannot be established with this study design due to the lack of a control group. Most cats were colonized with mixed Helicobacter species.